Bioterrorism: The Role of Genetics and Molecular Biology - Isna Rasdianah Aziz; Andika Saputra (Prosiding Seminar Biologi, 2017)
Science and technology can replace the ideology adopted to achieve human progress and prosperity. Development of bioterrorism is related to the development of genetic science and the development of biotechnology nowadays. One of the uses of biological agents as a tool of terror is the use of microbes that can be adapted into stealth viral vector which causes a variety of dangerous diseases for humans. Therefore, early awareness is needed about this case. Without the understanding and awareness of the community and the active role of the parties involved in dealing with the effects of bioterrorism, it will threaten national security such as security, public health and the economy